DPPH radical scavenging activity of moringa oleifera leaf extract and its protective effect on the shelf life of cherry tomatoes / Rosmawati Abdul Aziz …[et al.] - Abdul Aziz, Rosmawati; Syed Ismail, Syarifah Nursyimi Azlina; Mohamad Mahbob, Emi Norzehan; Mohd Shukri, Azizah (Universiti Teknologi MARA Cawangan Pahang, 2021)
Moringa oleifera Lam. which locally known as ‘pokok kelor’ is riched with flavonoids. In this study, the composition of the M. oleifera leaves ethanolic extracts was determined using Gas Chromatography-Mass Spectrometry (GCMS). The extraction method of ethanolic extract was done by a maceration process and the crude extract was obtained by rotary evaporator. The crude yield was 3.75 %. Four major compounds were identified including 1,2,3-triazole, beta-D-glucopyranosiduronic, octadecamethyl-cyclononasiloxane and pyrazole. Antioxidant capacity of the extracts through its DPPH radical scavenging activity was investigated using UV-Vis spectrophotometer at wavelength of 517 nm. IC50 for M. oleifera leaves extract is found to be 53.95 µg/ml compared to the standard ascorbic acid, 55.255 µg/. Moreover, this study also assessed the ability of the extracts in increasing the shelf life of tomato fruits. Coating of the extract with 80 ppm and 100 ppm substantially improved the shelf life of cherry tomato fruit with retaining better fruit quality attributes under room temperature.